866 Improving the Quality of Clinical Coding and Documentation to Record Accurate Outcomes in Non-Operatively Managed Hip Fractures. (19th August 2022) - Shrestha, S; Khatir, MAA; Iyengar, KP; Sangani, C
Abstract: Background: Our 2019 Clinical Audit for non-operatively managed hip fractures at our Trust was 9.76% against the national standard of 5% at The National Hip Fracture Database (NHFD) annual report 2017. A re-audit was conducted to review reasons for higher incidence as recommended by NICE and improve outcomes. Method: Hip fracture patients admitted between 1st April 2019 and 31st August 2020 to Southport and Ormskirk NHS Trust were reviewed clinico-radiologically. Data was collected from NHFD, EVOLVE patient records, and PACS imaging systems. Following appropriate "Primary Diagnosis" of hip fracture, confirmation of operative or non-operative management was undertaken following a joint assessment by the Orthopaedic staff and the Clinical Coding department evaluating reasons behind the decision. Secondary outcome measures compared 30-day and one-year mortality with the previous cohort. Results: In the re-audit, 512 cases were reviewed, 50 patients excluded following correct Clinical Coding, 440 hips were operated and 22 (4.8%) managed non-operatively. However, 30-day mortality rose from 30.5% during the audit to 54.50% possibly due to the effect of COVID-19. Conclusions: The newly introduced "Neck of Femur Proforma" has remarkably improved the quality and organization of clinical documentation of diagnosis. Appropriate Clinical Coding allows correct information for the NHFD Trust figures.